Radon levels in drinking water of Fatehabad district of Haryana, India. (May 2017) - Duggal, Vikas; Sharma, Samriti; Mehra, Rohit
Abstract: Radon concentrations were measured in 59 groundwater samples collected from Fatehabad district of Haryana, India. The measurements were performed by RAD7 an electronic radon detector manufactured by Durridge Company Inc. The measured radon concentration ranged from 1.4 to 22.6 Bq l −1 . 14% of the groundwater samples were above the United States Environmental Protection Agency recommended value for radon in water. The annual effective dose for ingestion and inhalation was also evaluated in this research. The total annual effective dose due to ingestion and inhalation of radon in drinking water varied from 14.1 to 221.8 µSv y −1 . Highlights: We report the radon concentration in 59 groundwater samples from Haryana. The water samples were characterized by RAD7 radon detector. A 14% of the groundwater samples were above the USEPA recommended value. Total annual effective dose from 12 locations was above EU Council recommendations.